Enhancing the Synergistic Pathways of Industrial Pollution and Carbon Reduction (PCR) in China: An Energy Efficiency Perspective - Zhiyuan Gao; Ziying Jia; Ying Zhao; Yu Hao (Energies)
Industry is a major contributor to air pollution and CO2 emissions, and a major force for reducing them. Based on the idea of improving the performance of the synergy effect “1 + 1 > 2”, this paper constructs a method that evaluates the synergistic effect of pollution and carbon reduction (PCR) in terms of energy efficiency under the framework of Data Envelopment Analysis (DEA) and analyzes the basic path of China’s synergistic effect of PCR from the viewpoint of energy efficiency. Based on the construction of a global non-radial directional distance function, we develop an emission performance measurement index for output factors. Furthermore, by comparing performance changes under individual and collaborative emission reduction scenarios, we establish an evaluation model for assessing the synergistic effects of PCR. The results show the following: (1) Collaboration between PCR enhances both the air pollution emission performance and carbon dioxide emission performance in China. (2) The synergistic effect of collaborative emission reduction is universal in different regions and provinces. However, the synergistic effect of PCR found in the east, central, and west has strong heterogeneity. (3) Different improvement pathways, such as prioritizing energy conservation or carbon mitigation, were designed to account for regional development disparities. Although these policy orientations can effectively enhance the synergy between pollution control and carbon mitigation, the extent of improvement varies considerably across regions.